Evident-based therapeutic effects of anthocyanins from foods - Khoo, Hock Eng; Lim, See Meng; Azlan, Azrina (Asian Network for Scientific Information, 2019)
This review covers potential health benefits and efficacies of anthocyanins as well as anthocyanidins, in the prevention of several diseases. Blue, red and purple coloured fruits, vegetables and grains are rich in anthocyanins and have several health benefits, such as prevention of chronic diseases, antimicrobial, antioxidative and anti-inflammatory effects as well as improve vision and memory. Various in vitro and in vivo studies demonstrated the efficacy of anthocyanins in fruits and vegetables for the prevention of diseases and other health benefits. Most of the studies showed positive results towards the improvement of disease conditions. In short, anthocyanins and the anthocyanin-rich extracts are some of the best remedies used in prevention of several diseases, memory enhancement and behavioural improvement.